BCAS2 is involved in alternative splicing and mouse oocyte development. Issue 2 (31st December 2021) - Zhang, Jiaqi; Liu, Wenbo; Li, Guangyue; Xu, Chengpeng; Nie, Xiaoqing; Qin, Dandan; Wang, Qizhi; Lu, Xukun; Liu, Jianqiao; Li, Lei
Abstract: Alternative splicing (AS) is an important mechanism to regulate organogenesis and fertility. Breast carcinoma amplified sequence 2 (BCAS2) is one of the core components of the PRP19 complex, a multiple function complex including splicing, and it is involved in the initiation of meiosis through regulating AS in male mice. However, the role of BCAS2 in mouse oogenesis remains largely unknown. In this study, we found that BCAS2 was highly expressed in the oocytes of primordial follicles. Vasa ‐ Cre ‐mediated deletion of Bcas2 caused poor oocyte quality, abnormal oogenesis and follicular development. The deletion of Bcas2 in mouse oocytes caused alteration in 991 AS events that corresponded to 706 genes, including Pabpc1l, Nobox, Zfp207, Mybl2, Prc1, and Spc25, which were associated with oogenesis and spindle assembly. Moreover, the disruption of BCAS2 led to degradation of PRP19 core proteins in mouse oocytes. These results suggested that BCAS2 was involved in the AS of functional genes through PRP19 complex during mouse oocyte development.